Deadbeat Control of a Modified Single-Phase Five-Level Photovoltaic Inverter with Reduced Number of Switches - Mohsen Ghorbanali Afjeh; Mojtaba Babaei; Mohsen Alizadeh Bidgoli; Amir Ahmarinejad (International Journal of Photoenergy)
In this article, a modified single-phase five-level photovoltaic inverter is proposed with a single DC voltage source and six semiconductor switches. Compared with the presented inverters, the introduced topology has the advantage of decreased device count and the first switching frequency for high blocking voltage switches. The proposed PV inverter is implemented without clamping diodes and transformers, which leads to a decrement in size and, consequently, the weight of the converter. In addition, for the proposed topology, space vector pulse width modulation (SVPWM) is deployed that reduces the complexity of multilevel modulation. In order to obtain the optimal output voltage of the inverter, the deadbeat controller is suggested as a rapid dynamic, low-computation digital control method. This closed-loop inverter is implemented in TMS320f28335 digital signal controller to evaluate the performance of the proposed inverter under nonlinear and linear loads. Simulation and laboratory prototype results show that IEC 62040-3 harmonic constraints is met for the proposed photovoltaic inverter in standalone applications.